Le féodalisme dans la vallée du Saint-Laurent: Un problème historiographique - Matteo Sanfilippo; Olivier Guimond; Arnaud Montreuil; Michel Bock (Les Presses de l'Université d'Ottawa/University of Ottawa Press, 2022)
Is the history of Laurentian seigneuries the offspring of political conflict? This question, and many others, are among those addressed in Le féodalisme dans la vallée du Saint-Laurent. In this work, Sanfilippo summarizes and analyzes 250 years (1763–2008) of historiographical production in French and English Canada that deals with the Laurentian seigneurial regime. But the goal of the book is also to put the historians' discourses on the seigneurial regime back into their respective political contexts. By doing so, the author firmly demonstrates how the history of this regime is inextricably linked to Canadian political dynamics. The result of an objective look by an Italian historian who studied English and French works for many years, Le féodalisme dans la vallée du Saint-Laurent is also a unique essay in the Canadian historiographical landscape now translated into French. At a time of clear revival in seigneurial history, readers will discover the captivating story of Laurentian seigneuries and encounter Sanfilippo's opinions. The postface, written by Olivier Guimond and Arnaud Montreuil, pursues Sanfilippo's reflections from 2008 to today.